1979
DOI: 10.1128/jb.138.1.109-117.1979
|View full text |Cite
|
Sign up to set email alerts
|

Change from Homo- to Heterolactic Fermentation by Streptococcus lactis Resulting from Glucose Limitation in Anaerobic Chemostat Cultures

Abstract: Lactic streptococci, classically regarded as homolactic fermenters of glucose and lactose, became heterolactic when grown with limiting carbohydrate concentrations in a chemostat. At high dilution rates (D) with excess glucose present, about 95% of the fermented sugar was converted to L-lactate. However, as D was lowered and glucose became limiting, five of the six strains tested changed to a heterolactic fermentation such that at D = 0.1 h-1 as little as 1% of the glucose was converted to L-lactate. The produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
156
1
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(181 citation statements)
references
References 27 publications
18
156
1
3
Order By: Relevance
“…(1) lactate dehydrogenase: pyruvate + NADH -~ r,-lactate + NAD ( Fig. 1A) (2) pyruvate formate lyase: pyruvate --* acetyl-P + formate ( Shifts in product formation from lactose, glucose and pyruvate upon aeration, changing of the pH or cultivation under carbohydrate limitation are generally observed in different homofermentative lactic acid bacteria [50][51][52][53]. The complex mechanisms that are involved in regulation of pyruvate metabolism L. lactis will be discussed below.…”
Section: Pyrmate Metabolismmentioning
confidence: 99%
“…(1) lactate dehydrogenase: pyruvate + NADH -~ r,-lactate + NAD ( Fig. 1A) (2) pyruvate formate lyase: pyruvate --* acetyl-P + formate ( Shifts in product formation from lactose, glucose and pyruvate upon aeration, changing of the pH or cultivation under carbohydrate limitation are generally observed in different homofermentative lactic acid bacteria [50][51][52][53]. The complex mechanisms that are involved in regulation of pyruvate metabolism L. lactis will be discussed below.…”
Section: Pyrmate Metabolismmentioning
confidence: 99%
“…The study of the nutritional requirements of lactic acid bacteria has been made possible following the early development of chemically defined media allowing growth of Lactococcus lactis [7][8][9][10][11] or various species of lactobacilli including some of those used in food fermentations [12][13][14][15]. All these media contain, in addition to mineral salts and glucose, amino acids, vitamins and nu-cleic acid bases.…”
Section: Amino Acid Requirements and Biosynthetic Capabilities Of Lacmentioning
confidence: 99%
“…For example, several lactic streptococci accumulate substantial amounts of formate, ethanol and acetate and correspondingly less lactate when grown in glucose-or lactose-limited unaerated chemostat cultures, whereas with excess sugar the same cultures are homolactic. The production of products other than lactate in the sugar-limited cultures is attributed to relatively low intracellular levels of fructose-l,6-bisphosphate (FBP), an essential activator of lactate dehydrogenase in these strains [60]. The presence of 0 2 often has significant effects on the metabolism of pyruvate in these and other LAB.…”
Section: -Induced Alterations In Pyruvate Transformation In Lactic mentioning
confidence: 99%
“…The operation of this pathway varies among LAB. Thomas et al [60] found that most Group N streptococci produced formate, acetate and ethanol from glucose or lactose in unaerated chemostat cultures only when the sugar was limit-ing and FBP levels were low. However, some oral streptococci accumulate these end-products even when glucose is in excess in strictly anaerobic conditions.…”
Section: The Pyruvate Formate-lyase Pathway To Formate Acetate and Ementioning
confidence: 99%